2020
DOI: 10.1007/s13300-020-00885-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium-Glucose Cotransporter-2 Inhibitors on Endothelial Function: A Systematic Review of Preclinical Studies

Abstract: Introduction: While the beneficial effects of sodium-glucose cotransporter-2 (SGLT-2) inhibitors on cardiovascular and renal outcomes are recognized, their direct effects on endothelial function remain unclear. We, therefore, undertook a systematic review to evaluate the current literature in this area. Methods: Electronic databases (PubMed, EMBASE, and Medline) were systematically searched using PRISMA guidelines for studies involving the in vitro, in vivo, or ex vivo administration of SGLT-2 inhibitors to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 64 publications
1
47
0
1
Order By: Relevance
“…Several mechanism(s), most of them proven in both human and animal models, have been proposed as responsible for the benefits on cardiovascular risk of SGLT2 inhibition [ 2 ], including diuresis/natriuresis that lead to blood pressure reduction, enhanced cardiac energy metabolism, reduction of inflammation reduction, inhibition of the sympathetic nervous system, prevention of ischemia/reperfusion injury, decreasing epicardial fat mass, decreasing oxidative stress and improvements on vascular function, among others [ 2 , 9 , 10 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanism(s), most of them proven in both human and animal models, have been proposed as responsible for the benefits on cardiovascular risk of SGLT2 inhibition [ 2 ], including diuresis/natriuresis that lead to blood pressure reduction, enhanced cardiac energy metabolism, reduction of inflammation reduction, inhibition of the sympathetic nervous system, prevention of ischemia/reperfusion injury, decreasing epicardial fat mass, decreasing oxidative stress and improvements on vascular function, among others [ 2 , 9 , 10 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this might be a temporal effect as the benefits within the heart failure group have only recently been incorporated into international (EASD/ADA) guidelines and have yet to be included as part of the treatment algorithm in the UK based NICE guidelines for type 2 diabetes, which focus principally on improving glycaemic control [ 11 , 15 ]. There is accumulating data on the benefits of SGLT-2is on cardiac function, vascular endothelial function, and cardio-metabolic risk factors [ 38 43 ], which may further enhance utilisation of these drugs in real-world clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several cell-signaling pathways are involved in its pleiotropic action and lead to cardiovascular benefits. First, activation of the PI3K/AKT pathway decreases ROS generation and increases the phosphorylation of AKT/eNOS, which reduces inflammation and increases NO production [ 103 ]. Li et al reported that phlorizin suppressed the expression of SGLT-1 and SGLT-2, activated the PI3K/AKT/eNOS signaling pathway, and increased the output of NO in palmitic acid–incubated human vascular endothelial cells [ 104 ].…”
Section: Sodium-glucose Transporter-2 Inhibitorsmentioning
confidence: 99%